Relativistic X-Ray Jets from the Black Hole X-Ray Binary MAXI J1820+070 - Espinasse, M.; Corbel, S.; Kaaret, P.; Tremou, E.; Migliori, G.; Plotkin, Richard; Bright, J.; Tomsick, J.; Tzioumis, A.; Fender, R.; Orosz, J.A.; Gallo, E.; et al. (IOP PUBLISHING LTD, 2020)
The black hole MAXI J1820+070 was discovered during its 2018 outburst and was extensively monitored across the electromagnetic spectrum. Following the detection of relativistic radio jets, we obtained four Chandra X-ray observations taken between 2018 November and 2019 June, along with radio observations conducted with the Very Large Array and MeerKAT arrays. We report the discovery of X-ray sources associated with the radio jets moving at relativistic velocities with a possible deceleration at late times. The broadband spectra of the jets are consistent with synchrotron radiation from particles accelerated up to very high energies (>10 TeV) by shocks produced by the jets interacting with the interstellar medium. The minimal internal energy estimated from the X-ray observations for the jets is ∼1041 erg, significantly larger than the energy calculated from the radio flare alone, suggesting most of the energy is possibly not radiated at small scales but released through late-time interactions.